Politics and the media : harlots and prerogatives at the turn of the milennium (Oxford, UK ; Malden, MA : Blackwell, 1998)
This book consists of many essays about Politics and Media.
Keywords: Great Britain; Mass media; Political aspects; Mass media -- Political aspects -- Great Britain; Press and politics -- Great Britain -- History -- 20th century; Great Britain -- Politics and government -- 1979-1997.